Pentingnya Survei Analisa Kebutuhan Pelatihan (Training Need Assessment -TNA) Terkait Gizi untuk Peserta MSIB di SEAMEO RECFON - Kamalia, Hijriah; Elvandari, Millyantri (Innovative: Journal Of Social Science Research, 2024)
Students in the age range of 19-29 years are an early adult group that is vulnerable to various factors such as uncontrolled food intake, lifestyle changes, high environmental pressure, lack of physical activity, and high levels of stress due to the pressure of college education. The purpose of this study is to identify the importance of nutrition-related training needs for MSIB students at SEAMEO RECFON. The method used involves comparing and reviewing the content and conclusions of each theory contained in the articles. These articles are obtained from books related to the implementation method of Training Needs Assessment (TNA). Providing nutrition training and education to young adults, namely students, is expected to increase awareness of the importance of knowing nutritional status in their lives, so as to minimize less productive students who will have an impact on performance when studying and working.